THE EFFECT OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH LEADER SUPPORT AS A MODERATING VARIABLE AT PANCA BUDI COLLEGE MEDAN - Abdi Setiawan; Prihatin Lumbanraja; Yeni Absah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Achieving satisfactory performance requires professional skills, and to achieve them, several stages or conditions must be passed. Formal education is still inadequate to achieve professional skills. Therefore, employee capabilities must be empowered through training, education, and development. Assessments of high-achieving employees and awards for employee performance provide encouragement and encourage employees to continue their education to a higher level, and superiors provide reprimands if employees do not complete work on time. However, leadership support is not running well because not all employees are assessed according to their achievements and the lack of information to other employees results in some employees' work not being completed within the specified time. The purpose of this study is to determine and analyze the effect of training and work motivation partially on employee performance at Panca Budi Medan College. Knowing and analyzing the effect of leader support as a moderating variable can strengthen the influence of training and work motivation on employee performance at Panca Budi Medan College. Data collection in this study was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 46 people. The data analysis method used is multiple linear regression with data processing through SPSS (Statistical Package for Social Science). The results of the study indicate that simultaneously training and work motivation have a positive and significant effect on the performance of employees at Panca Budi Medan College. Partially, training has a positive and significant effect on the performance of employees at Panca Budi Medan College. Partially, work motivation has a positive and significant effect on the performance of employees at Panca Budi Medan College. The results show that training is the dominant factor influencing employee performance. Leader support is not a moderating variable that strengthens the influence of training and work motivation on employee performance. The results of the determination coefficient (adjusted R square) indicate that the ability of training and work motivation to explain variations in employee performance is quite strong, while the rest is influenced by other variables outside the variables studied, such as work discipline and compensation.